The digital archiving of music at the Danish Broadcasting Corporation: History, ideals, taxonomy - Helles Pedersen, Andreas (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2022)
This article offers a history of the digital music archive at the Danish Broadcasting Corporation (DR). By looking into archival documents, reviewing interviews and analyzing interfaces, the article examines visions and strategies behind the digital music archive and its in-house platform, /Diskoteket, and based on this the article assesses whether or not DR’s archival strategies play an active role in creating an institutionalized understanding of music history. The article considers how music metadata are operationalized in the digital music archive’s database, and from this it casts light on the ways that /Diskoteket balances several, and somewhat opposing, music histories. The processes of music archiving at DR are viewed as a continuous production of a causal history side by side with non-linear chronologies that follow a relational perspective, and it is argued that the digital music archive hints at a promise of thinking anew of recorded music’s pasts. In conclusion, the article speculates on DR’s options for carving out a position of relevance in the field of music communication in the future that relies on a strengthening of the operationalized metadata, which ought to be made available to the public.